Developing Comic Strips as Elt Materials For Speaking Practice Using the Addie Model - Rum Puspita Budi Andamari (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This research was intended to design a supplementary material using comic strips for speaking practice. Since English is used as an international language as a communication tool, English learners in Indonesia are now expected to develop their speaking abilities. To build their speaking abilities, learners should challenge themselves to speak English. Meanwhile, in most textbooks, the speaking materials are limited to brief explanations and are usually presented in the form of tasks, especially from the textbook "Work in Progress”. This book is one of the compatible books for the emancipated Curriculum, but the materials are not interesting for learners, which leads to a lack of motivation to learn.
Repo 16 Juli 2026_ Rudy K :: Finalisasi file repositori 16 Juli 2026_Kurnadi
Keywords: Developing Comic Strips as ELT